Low voltage 25Gbps silicon Mach-Zehnder modulator in the O-band - Pérez-Galacho, Diego; Baudot, Charles; Hirtzlin, Tifenn; Messaoudène, Sonia; Vulliet, Nathalie; Crozat, Paul; Boeuf, Frederic; Vivien, Laurent; Marris-Morini, Delphine (Optical Publishing Group, 2017)
In this work, a 25 Gb ps silicon push-pull Mach-Zehnder modulator operating in the O-Band (1260 nm - 1360 nm) of optical communications and fabricated on a 300 mm platform is presented. The measured modulation efficiency (Vπ Lπ) was comprised between 0.95 V cm and 1.15 V cm, which is comparable to the state-of-the-art modulators in the C-Band, that enabled its use with a driving voltage of 3.3 Vpp, compatible with BiCMOS technology. An extinction ratio of 5 dB and an on-chip insertion losses of 3.6 dB were then demonstrated at 25 Gbps.
Keywords: Comunicaciones ópticas; Optoelectronics; Modulators; Optical interconnects